MANAJEMEN REPRODUKSI UNTUK MENCEGAH TERJADINYA KAWIN BERULANG DAN DISTOKIA PADA SAPI PASCA INSEMINASI BUATAN - I Wayan Lanus Sumadiasa; Adji Santoso Dradjat; Lalu Ahmad Zaenuri; Rodiah Rodiah; Enny Yuliani (Jurnal Abdi Insani, 2023)
The application of artificial insemination (AI) technology using exotic bovine semen often causes pregnancy failure, abortion, disocia and other birth disorders. The result is frequent repeated mating, losses in terms of energy, cost and time, delays in regeneration during productive life, and reproductive inefficiencies. The problem is, farmers do not know much about the factors that cause AI results to fail, so they need to be given counseling. Providing information, understanding and skills to the public on ways to manage reproduction properly and correctly to prevent re-mating and dystocia in cattle after artificial insemination. The activity was carried out using a participatory method through counseling, discussion and brief coaching, taking place in Sintung Village which is the activity center and secretariat of farmer-livestock groups in the Pringgarata District. The target audience is the heads and members of farmer-livestock groups and other farming communities. Community service is quite successful. The participants were very interested in the material presented. After counseling the participants obtained information, understanding and skills to increase the success of IB. Participants were educated on how to select prospective broodstock recipients, choose the type of male semen, management of pregnant sows, pregnant cages and delivery. Need marriage records, know the signs and predictions of birth, birth handling by a veterinarian or veterinary paramedic. The supporting factor for the activity was the enthusiasm of the counseling and discussion participants, while the inhibiting factor was the massive outbreak of PMK in almost all sub-districts which limited the freedom of activity a bit. Service activities run well and smoothly. The participants benefited from the knowledge of reproductive management to prevent re-mating.